Design and Characterization of Microwave Irradiation Assisted Amorphous Solid Dispersion of Resveratrol - Sai, Lakshmi Swapna; Dasankoppa, Fatima Sanjeri; Sholapur, Hasanpasha N; Sagare, Revati Dharampal (Indian Journal of Pharmaceutical Education and Research, 2025)
Background One of the emerging solutions for facing the solubility as well as dissolution issues of poorly soluble drugs is formulation approach by dispersing drugs in hydrophilic carriers. Objectives Present study aims in enhancing the solubility of resveratrol by amorphous solid dispersion technique. Materials and Methods Solid dispersions were prepared by microwave irradiation where the irradiation time and the drug: carrier ratios were optimized using Design of Experiments by the effect of these critical parameters on solubility as a response variable. Results and Discussion Solubility of the fabricated amorphous solid dispersions were analyzed and optimized at 1:5 drug: carrier ratio with an irradiation time of 5 min. Different characterization techniques like infrared spectroscopy, particle size, differential scanning calorimetry etc., were performed in order to study and prove the process of amorphization. The results of powder X-ray diffraction studies, scanning electron microscopic studies certainly highlighted the conversion of crystalline form of resveratrol into an amorphous form along with reduced particle size of 41 times in solid dispersion than that of pure resveratrol. Conclusion With the present work, it can be concluded that microwave irradiation is an absolute approach in preparation of amorphous solid dispersions.
Keywords: Microwave irradiation; Amorphous solid dispersion; Resveratrol; Soluplus; Design Expert; Solubility enhancement.